Música aos corações: um tourbillon social nas óperas de Jean-Jacques Rousseau - Calderazzo, Angela de Campos Machado Vessoni (2008)
By the immanent analysis of the libretti, scores and recordings of the operas La découverte du nouveau monde, Le devin du village, Daphnis et Chloé, Les muses galantes, Pygmalion, romances and motets, composed by Jean-Jacques Roussseau, our work s theme is the history of the Enlightenment society through the composer s critic to what he named tourbillon social. Such critic was built on the hypothesis of a state of nature foreseen to correct a turbulent and corrupt society. Our starting point is the idea that Rousseau s sensitivity, as an artist of the XVIII th. Century, explains a paradoxal world and expresses a contradiction which opposes the natural to the modern . It is an idealization that confronts nature with the corrupt society; that materializes, in music and text, a modern vision of world, which moved away from a state of nature idealized by the composer. A design about the bourgeois world of the XVIII th. Century, and about the way a woman behaved in that social dynamics